Didactical Situation of Learning Integer Material Based on Local Culture to Support Student Numeracy Literacy - Yohanis Ndapa Deda; Hermina Disnawati; Otaget Daniel; Suhendra; Darhim (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
Didactically oriented research that considers the relationship between teachers, students and materials was vital. This research aimed to obtain an overview of the didactical situation in the learning process of whole number concepts as a basis for designing appropriate learning designs based on local culture for junior high school students in North Central Timor. The research method followed the stages of Didactical Design Research (DDR). The research instruments were observation sheets, interview guidelines, and documentation. Data analysis included prospective analysis, observation data, and post-observation data. The results revealed that student preparedness for learning posed a barrier to the otherwise smooth operation of instructor, student, and material interactions. Learning the concept of mixed operations of whole numbers was successful in terms of learning objectives achieved and learning that took place according to plan. The research concluded that the existence of the Topaze Effect and the Aging of Teaching Situations when learning whole number operations in the classroom. Didactical situated research contributes to define the scope and substance of didactics, focusing on the shared values and knowledge that underpin effective numbers instruction. Keywords: Didactical Situation, Integers, Local Culture, Numeracy Literacy